2015
DOI: 10.1590/s0100-83582015000300004
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Ability of Canola Hybrids With Weeds

Abstract: -The objective of the study was to assess the relative competitive ability of canola hybrids in the presence of turnip (Raphanus sativus) and ryegrass (Lolium multiflorum) in different ratios of plants in the mixture. The experiments were conducted in a greenhouse, in a completely randomized design with four replications. Treatments were arranged in ratios of canola against turnip or ryegrass: 100:0, 75:25, 50:50, 25:75 and 0:100. Competitive analysis of the species was accomplished by means of diagrams usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
(47 reference statements)
0
12
0
5
Order By: Relevance
“…In an experiment carried out comparing the competitive ability of Hyola 61, Hyola 76, Hyola 433 and Hyola 571CL canola hybrids with the turnip, the authors verified that there was mutual injury to the growth of the crop and weed, being observed concave lines for PR of both (Galon et al, 2015). Still in this trial, the authors found PRT lower than 1, indicating that competition between canola and turnip caused mutual injury.…”
Section: Resultsmentioning
confidence: 89%
“…In an experiment carried out comparing the competitive ability of Hyola 61, Hyola 76, Hyola 433 and Hyola 571CL canola hybrids with the turnip, the authors verified that there was mutual injury to the growth of the crop and weed, being observed concave lines for PR of both (Galon et al, 2015). Still in this trial, the authors found PRT lower than 1, indicating that competition between canola and turnip caused mutual injury.…”
Section: Resultsmentioning
confidence: 89%
“…The morphological and physiological traits of each canola hybrid influence their competitive ability against weed species. Galon et al (2015) reported that Hyola 433 (used as volunteer hybrid in this study) was more competitive than Hyola 61 in association with turnip; however, in the interaction with ryegrass, Hyola 61 showed the highest competitive ability between all hybrids tested.…”
Section: Resultsmentioning
confidence: 56%
“…The ryegrass is commonly found in the crops of the southern region of Brazil, this species has elevated seed production and easy dispersion, causes losses of wheat production (Agostinetto et al, 2008), in barley (Tironi et al, 2014) and in canola (Galon et al, 2015). It is noteworthy that scarce are the studies that have evaluated the competition effect of turnip and ryegrass on onion culture, thus justifying the present work.…”
Section: Introductionmentioning
confidence: 75%